A real‐world study to assess the association of cardiovascular adverse events (CVAEs) with ibrutinib as first‐line (1L) treatment for patients with chronic lymphocytic leukaemia (CLL) in the United States. Issue 1 (23rd January 2023) - Mato, Anthony; Tang, Boxiong; Azmi, Soraya; Yang, Keri; Han, Yi; Zhang, Xiaowei; Roeker, Lindsey; Wallis, Nicola; Stern, Jennifer C.; Hedrick, Eric; Huang, Jane; Sharman, Jeff P.
Abstract: Ibrutinib, a Bruton's tyrosine kinase inhibitor, is often used as first‐line (1L) treatment of chronic lymphocytic leukaemia (CLL); however, it is associated with an increased risk for cardiovascular adverse events (CVAEs). This real‐world study adds to existing literature by simultaneously investigating the correlation between pre‐existing CV risk factors and the relative cardiotoxicity of ibrutinib vs other therapies in CLL/small lymphocytic lymphoma (SLL). Using a real‐world database, the risk of subsequent CVAEs (any CVAE, atrial fibrillation [AF], or hypertension) were compared among patients who received 1L ibrutinib monotherapy or another type of non‐ibrutinib therapy, grouped as intensive (IT) or non‐intensive therapy (NIT). Each patient's baseline CV risk was estimated using the Framingham risk score. Inverse probability treatment weighting was incorporated into a logistic regression model to reduce baseline imbalance. Results showed ibrutinib was significantly associated with higher risk of CVAEs regardless of baseline CV risk. Compared with IT, odds ratios of any CVAE, hypertension, or AF were 2.61, 3.66, and 3.02, respectively vs 1.88, 2.13, and 2.46, respectively, with NIT. Sensitivity analyses confirmed the findings were robust. These results suggest clinical caution should be taken when selecting ibrutinib for patients with CLL/SLL, especially in those with high baseline CV risk.